RELATIVE FECUNDITY, FERTILIZATION DEGREE AND HATCHING DEGREE OF FEMALE GOLDFISH (Carassius auratus) WITH RANGRANG ANTS EGG (Oecophylla smaragdina) AND OOCYTE DEVELOPER COMBINATION - Mutiara Wahyuni; Munti Sarida; Deny Sapto Chondro Utomo (University of Lampung, 2022)
Length of time entering readiness early reproduction so that the relative fecundity and the low degree of fertilization and the degree of hatching in the goldfish hatchery are a challenge in the effort to provide goldfish seeds in quality and quantity. The effort was made by combining kroto and oocyte developer in the female goldfish. This experiment was carried out in September 2019-March 2020 at the Aquatic Productivity Laboratory of the Faculty of Agriculture, University of Lampung. The test fish used were 60 females 5-month-old brood stock, with an average weight of 14.69±3.69 g. This study used a completely randomized design using two factors, kroto (g / kg of fish) and oocyte developer (ml / kg of feed) with two levels each: K1O1 (0 + 0), K2O1 (30 + 0), K1O2 (0 + 0.5), and K2O2 (30 + 0.5) and 3 replications for each treatment. The results showed that factor K (kroto) and factor O (oocyte developer) had no effect on the relative fecundity of female goldfish during 8 weeks of maintenance. Meanwhile, the combination of kroto and oocyte developer affected the relative fecundity of the female goldfish at the 8th week of rearing, the degree of fertilization, and the degree of hatching